2013
DOI: 10.1089/lap.2012.0301
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transperitoneal Versus Retroperitoneal Laparoscopic Adrenalectomy in a Prospective Randomized Study

Abstract: Laparoscopic adrenalectomy is a viable treatment option for removal of benign adrenal lesions that can be performed safely and effectively by either the transperitoneal or retroperitoneal approach. All operative parameters are similar in the two approaches, except that the convalescence period and time to oral intake resumptions that are significantly shorter with retroperitoneal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…In several studies, no significant differences in outcome variables were noted between the laparoscopic PRA versus the “classic” laparoscopic LTA [5, 1921]. Similar operation times were reported in early studies.…”
Section: Discussionsupporting
confidence: 55%
“…In several studies, no significant differences in outcome variables were noted between the laparoscopic PRA versus the “classic” laparoscopic LTA [5, 1921]. Similar operation times were reported in early studies.…”
Section: Discussionsupporting
confidence: 55%
“…Several operative parameters have been found to favour adrenalectomy performed via the retroperitoneal approach. These include shorter hospital stay [35363738], faster resumption of oral intake [3538], decreased analgesic requirement and postoperative pain which in turn leads to earlier ambulation [3739], shorter operative time [3739], blood loss [3839], and morbidity [40] associated with the procedure. The major benefit of the retroperitoneal approach is that with the adrenal against the ribcage at the back, there was no need to move any other organs out of the way.…”
Section: Transperitoneal Versus Retroperitoneal Adrenalectomymentioning
confidence: 99%
“…Several studies have been conducted to compare both surgical approaches. Several studies have shown that the outcomes of PRA were superior to TLA for removing adrenal tumors in terms of less blood loss and shorter operation time [9][10][11]. However, there is a lack of data regarding the comparison of the two approaches in patients with PHEO.…”
Section: Introductionmentioning
confidence: 99%